PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA PEMBUATAN ECOPRINT TEKNIK POUNDING DI MAN 2 MADIUN - Dyah Novia Fitrianingrum; Inty Nahari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Project Based Learning is a learning model based on projects. In this learning model, students are required to be active in the learning process, so that they can improve skills, creativity, and learning experiences through the completion of a project. This study aims to 1) describe the implementation of the Project Based Learning model in making ecoprint using the pounding technique, 2) describe the results of students’ ecoprint products using the pounding technique, and 3) describe students’ responses to the Project Based Learning model in the ecoprint-making material using the pounding technique. This study used a quantitative descriptive approach with a pre-experimental one shot case study design. The subjects of this study were 14 students in the Fashion Skills Program, Phase F, Grade XII. Data collection was carried out using learning implementation observation sheets, product assessment sheets, and student response questionnaires. The collected data were then analyzed using quantitative descriptive analysis techniques to provide an overview of the learning implementation, product results, and student responses. The results showed that 1) the implementation of Project Based Learning was classified as very good with an average score of 4.7; 2) the results of students’ ecoprint products had the lowest score of 78 and the highest score of 96, with 43% of students in the good category and 57% in the very good category; and 3) students’ responses to the implementation of Project Based Learning in ecoprint making were classified as very positive with an average percentage of 84.47%. These results indicate that the implementation of Project Based Learning can be carried out very well in the ecoprint-making material using the pounding technique.